2021
DOI: 10.3390/diagnostics11030542
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Axial Length and Corneo-Scleral Topography: A Preliminary Study

Abstract: The main objective of the current study was to investigate further the relationship of the overall length of the eye with a great variety of anterior segment parameters, including scleral geometry. A total of 64 eyes of 32 participants with ages from 12 to 52 years were included in this prospective non-randomized single-center study. All participants underwent a complete eye examination, including an analysis of corneo-scleral shape with a Fourier-domain profilometer. A strong negative correlation was found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, owing to the difficulty in measuring posterior scleral biomechanics in vivo , some researchers suggested measuring the anterior segment parameters instead of posterior scleral biomechanics to predict the development of myopia ( Hayashi et al, 2010 ; Long et al, 2019 ; Wu et al, 2019 ). Bataille et al investigated the relationship between AL and various anterior segment parameters and developed a model to predict AL; however, the author pointed out that a larger sample size was needed for validation ( Bataille et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to the difficulty in measuring posterior scleral biomechanics in vivo , some researchers suggested measuring the anterior segment parameters instead of posterior scleral biomechanics to predict the development of myopia ( Hayashi et al, 2010 ; Long et al, 2019 ; Wu et al, 2019 ). Bataille et al investigated the relationship between AL and various anterior segment parameters and developed a model to predict AL; however, the author pointed out that a larger sample size was needed for validation ( Bataille et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In severely elongated eyes, scleral thickness and rigidity are significantly reduced ( Sergienko and Shargorogska, 2012 ; Jonas et al, 2019 ). Some researchers believe that the eyeball is an integral organ, and the anterior segment parameters, including corneal biomechanics, are related to those of the posterior sclera ( Chansangpetch et al, 2017 ; Bataille et al, 2021 ). Previous studies found that high myopia can cause corneal biomechanical changes ( Moshirfar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monitoring corneal parameters could potentially serve as an early indicator for identifying children at risk of developing myopia. The exploration of the relationship between myopia and the extent of change in corneal parameters could provide valuable insights for predicting the future progression of myopia ( Wu et al, 2019 ; Bataille et al, 2021 ), which would be instrumental in myopia prevention and control strategies. Future research endeavors should consider the potential of corneal parameters in predicting the development of myopia in children, providing early warning for corneal parameter values in children who are likely to be myopic and guiding clinical interventions to prevent myopia as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Research has specifically demonstrated that increased axial length is associated with changes in the shape of the anterior sclera, as well as differences in the temporal-nasal ocular sagittal height for different chord lengths. 16,17 Additionally, Dhakal et al 18 demonstrated that the anterior sclera tends to become thinner inferiorly as myopia increases. Although these findings provide insight into the relationship between the anterior sclera and myopia, they do not describe fully how the three-dimensional (3D) anterior scleral shape changes with myopic development.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…While some studies reported no significant difference in scleral thickness with refractive error, 10,14,15 others have identified variations in the anterior sclera of myopic eyes. Research has specifically demonstrated that increased axial length is associated with changes in the shape of the anterior sclera, as well as differences in the temporal–nasal ocular sagittal height for different chord lengths 16,17 . Additionally, Dhakal et al 18 demonstrated that the anterior sclera tends to become thinner inferiorly as myopia increases.…”
Section: Introductionmentioning
confidence: 99%